2008
DOI: 10.2331/suisan.74.177
|View full text |Cite
|
Sign up to set email alerts
|

A study on the distribution of polyploid loaches in China

Abstract: Natural triploid and asexually reproducing clonal diploid loaches are found in Japanese populations of the loach, Misgurnus anguillicaudatus. The distribution of polyploid loaches in Chinese populations has not been studied except for a few cytogenetic studies that described the occurrence of polyploidy. In the present study, we examined the ploidy status of a total of 762 specimens collected from 29 localities in China by measurements of erythrocytic cell nucleus after the ploidy determination performed by ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 14 publications
0
26
0
Order By: Relevance
“…Tetraploid karyotype with 100 chromosomes was reported not only in the samples collected from Japanese fish markets and/or farm by Ojima and Takai (1979) and Arai et al (1991a), but also in the samples from Hubei Province, China by Li et al (1983), Yin et al(2005) and Li et al (2008Li et al ( , 2009). Ojima and Takai (1979) arranged 100 chromosomes to 10 M pairs, 4 SM pairs and 36 ST or T pairs, because they supposed that the entire genomes of tetraploid loach might have been already re-diploidized.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tetraploid karyotype with 100 chromosomes was reported not only in the samples collected from Japanese fish markets and/or farm by Ojima and Takai (1979) and Arai et al (1991a), but also in the samples from Hubei Province, China by Li et al (1983), Yin et al(2005) and Li et al (2008Li et al ( , 2009). Ojima and Takai (1979) arranged 100 chromosomes to 10 M pairs, 4 SM pairs and 36 ST or T pairs, because they supposed that the entire genomes of tetraploid loach might have been already re-diploidized.…”
Section: Discussionmentioning
confidence: 99%
“…Samples were killed after two injections of phytohemagglutinin (6 µg per g body weight) followed by one injection of colchicines (6 µg per g body weight), and gill tissues were fixed with Carnoy's solution after hypotonic treatment with 0.0375 M KCl according to previous studies (Lin 1982;Zhang 1993;Li et al 2008Li et al , 2009). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that they presumably have an exotic origin because continental Misgurnus loaches are being imported to Japan as food and tetraploid individuals with 100 chromosomes were reported in the specimens collected from Hubei Province in China (Li et al, 1983;2008).…”
Section: Diploid Sperm Of Natural Tetraploid Loachmentioning
confidence: 99%
“…In China, bisexually reproducing diploid (2n = 50)-tetraploid (4n = 100) complex exists and thus triploid hybrids are easily produced by cross-breeding (Li et al 2008(Li et al , 2010(Li et al , 2011(Li et al , 2012(Li et al , 2013). Since we observed that meiotic cells most frequently exhibited 25IIs and 25Is in triploid hybrids, we predicted the formation of gametes with a mode at 1.5n (37 or 38) chromosomes as a result of equal segregation of 25IIs and random segregation of 25Is (Li et al 2015).…”
Section: Introductionmentioning
confidence: 99%